Fontes de carboidratos para terminação de bovinos de corte: desempenho e características da carcaça e da carne - Freitas, Leandro da Silva (2012)
The objective of this study was to evaluate the effect of three carbohydrate sources (corn, soybean hulls or wheat bran) in the diet on performance, carcass characteristics and meat and the components are not part of the carcass of steers finished on confinement. We used 24 steers, crossbred Charolais x Nellore, with initial age of 22 months of initial body weight 353.2 ± 10.6 kg. The animals were fed a diet with roughage: concentrate 40,2:59,8, and the volume consisting of sorghum silage. The daily intakes of DM and CP were not influenced by sources of carbohydrates. Animals fed soybean hulls had higher intake of NDF and ADF, whereas calves receiving corn consumed higher levels of NFC, and TDN ED. Animals fed corn or soybean hulls had greater weight gain and better feed conversion than steers receiving wheat bran. The slaughter weight was similar between the sources of carbohydrates, averaging 429.81; 433.18 and 430.46 kg for maize, soybean hulls and wheat bran, respectively. The weight cut sidecut was greater for steers fed corn diet compared with soybean hulls or wheat bran. The meat from the diet with soybean hulls had better flavor compared to the wheat bran. The loss of the cooking liquid and cholesterol content were higher in animals treated with maize as compared to those receiving soybean hulls or wheat bran. There was no effect of carbohydrate sources on the weights of vital organs and blood. The absolute and relative weights to the weight of empty body fat of the intestines and rumen were higher in animals fed with corn. The weight of the omasum was greater for the diet with wheat bran, while animals fed soybean hulls had higher absolute weight of kidney fat.